Obtaining, characterizing and using genipin as a crosslinking agent for chitosan hydrogels (Research, Society and Development, 2021)
A variety of hydrogels, which correspond to a class of highly hydrated polymeric materials, are being used as biomaterials. In particular, chitosan hydrogels stand out for being an adhesive matrix that presents antibacterial, osteogenic and non-toxic properties. And they are able to retain, release and deliver therapeutic agents at the application site. The production of chitosan-based hydrogels has been achieved by mixing chitosan solutions with crosslinking agents or charged polymers under specific reaction conditions. The most commonly used reagent is glutaraldehyde, however, it has high cytotoxicity, and therefore, it has been replaced by less toxic and biologically safe crosslinkers, such as genipin, a natural reagent. Therefore, the objective of this work was to promote the extraction and purification of genipin in solid form from green fruits of Jenipapo, carrying out its identification through thin layer chromatography (TLC), mass spectrometry, infrared spectroscopy with transform Fourier test (FTIR) and quantification by gravimetric analysis. And the production of chitosan hydrogels using the obtained genipin as a crosslinking agent. The samples obtained were characterized by water absorption, Differential Scanning Calorimetry (DSC), FTIR and Rheology. The extracted genipin showed 0.47% extractive yield, while the hydrogels produced with 3% genipin showed a characteristic profile of a polymeric gel.